Association of habitual dietary intake with morningness-eveningness and rotating shift work in Japanese female nurses. (4th March 2018) - Yoshizaki, Takahiro; Komatsu, Taiki; Tada, Yuki; Hida, Azumi; Kawano, Yukari; Togo, Fumiharu
ABSTRACT: Rotating shift workers are associated with imbalanced dietary intakes. Rotating shift workers and dietary intakes in adults who do not engage in night work have also been shown to be associated with chronotype. However, no studies have examined associations between morningness-eveningness (i.e., the degree to which people prefer to be active in the morning or the evening), rotating shift work and dietary intakes. Therefore, our first purpose was to elucidate the association between morningness-eveningness and habitual food group intakes in rotating shift workers. The second purpose was to elucidate the association of morningness-eveningness and rotating shift work with food group intakes, considering habitual sleep durations. Japanese nurses (1095 day workers and 1464 rotating shift workers) were studied using a self-administered questionnaire. The questionnaire covered habitual dietary intakes, morningness-eveningness and demographic characteristics of the participants. A Japanese version of the Morningness-Eveningness Questionnaire (MEQ) was used to measure self-rated morningness-eveningness. Dietary intakes over the previous 1 month were evaluated using a semi-quantitative food frequency questionnaire. Intakes of pulses, green/yellow vegetables, white vegetables, fruits, algae, eggs, confectioneries/savory snacks and sugar-sweetened beverages were significantly ( p  < 0.05) associated with the MEQ score in rotating shift workers. Among these food groups, intakes of green/yellow vegetables, white vegetables, fruits and algae were significantly ( p  < 0.05) lower in rotating shift workers than in day workers, and intakes of confectioneries/savory snacks and sugar-sweetened beverages were significantly ( p  < 0.05) higher in rotating shift workers than in day workers. Intakes of these food groups were also significantly ( p  < 0.05) associated with the MEQ score in day workers. In addition, the MEQ score was significantly ( p  < 0.05) lower in rotating shift workers than in day workers, indicating greater eveningness among rotating shift workers. Multivariate linear regression revealed that the MEQ scores were significantly ( p  < 0.05) associated with intakes of these food groups, while rotating shift work was associated only with confectioneries/savory snacks. These results suggest that morningness-eveningness is associated with unbalanced dietary intakes in rotating shift workers as well as day workers, which may partially explain associations between rotating shift work and unfavorable dietary intakes. These findings have important implications for the development of novel strategies for preventing poor health caused by imbalanced dietary intakes in rotating shift workers.